Effects of the Histone Methyltransferase Inhibitor UNC0638 on Histone H3K9 Dimethylation of Cultured Ovine Somatic Cells and Development of Resulting Early Cloned Embryos. Issue 2 (28th January 2014) - Fu, L; Yan, F‐X; An, X‐R; Hou, J
Contents Aberrant hypermethylation of histone H3 lysine 9 (H3K9) may be involved in the developmental failure of cloned embryos. UNC0638 is a type of small molecule that can specifically inhibit the enzyme activity of histone methyltransferase EHMT2 and reduce the H3K9 dimethylation (H3K9me2) levels in cells. The objective of this study was to investigate the effect of UNC0638 in regulating H3K9me2 and development of cloned embryos. Results showed that UNC0638 could efficiently reduce H3K9me2 levels of cultured sheep foetal fibroblast cells in a concentration‐dependent manner. Cloned embryos were subsequently produced from UNC0638‐treated donor cells with down‐regulated H3K9me2, but their in vitro development was not improved when compared with the control. Our study suggested that revision of the single histone H3K9me2 modification may be not sufficient for rescuing the development of cloned embryos. However, because of its low cellular toxicity, UNC0638 may still be a potential chemical that could be used in regulating epigenetic modification of cloned embryos.